2019
DOI: 10.1038/s41594-019-0191-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of broad ebolavirus neutralization by a human survivor antibody

Abstract: The structural features that govern broad-spectrum activity of broadly neutralizing, anti-ebolavirus antibodies (Abs) outside of the internal fusion loop epitope are currently unknown. Here we describe the structure of a broadly neutralizing human monoclonal Ab (mAb), ADI-15946, which was identified in a human survivor of the 2013–2016 outbreak. The crystal structure of ADI-15946 in complex with cleaved Ebola virus glycoprotein (EBOV GP CL ) reveals that binding of the mAb structurally m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…The base-binding antibodies c2G4 and c4G7 [31,32] also stabilized the low-FRET state, to a greater extent than KZ52 (Figure 5a). In contrast, ADI-15946, an antibody that competes with KZ52 but bridges the GP1 core and glycan cap [33][34][35], modestly stabilized the high-FRET state. We also tested nAbs ADI-15878 and ADI-15742, which contact the GP2 fusion loop and adjacent GP1 protomer [33,34,36].…”
Section: Neutralizing Antibodies Mediate Gp Conformationmentioning
confidence: 86%
“…The base-binding antibodies c2G4 and c4G7 [31,32] also stabilized the low-FRET state, to a greater extent than KZ52 (Figure 5a). In contrast, ADI-15946, an antibody that competes with KZ52 but bridges the GP1 core and glycan cap [33][34][35], modestly stabilized the high-FRET state. We also tested nAbs ADI-15878 and ADI-15742, which contact the GP2 fusion loop and adjacent GP1 protomer [33,34,36].…”
Section: Neutralizing Antibodies Mediate Gp Conformationmentioning
confidence: 86%
“…Cleavage removes the glycan cap with the b17-b18 loop and exposes the pocket, which explained enhanced binding of rEBOV-520 to GP CL ( Figure 1C) and enhanced neutralization potency of this mAb against virions bearing the GP CL compared with intact GP . Previous work suggested that binding of the non-neutralizing macaque mAb FVM09 to the b17-b18 loop itself displaces the loop causing unmasking of the neutralizing epitopes for mAbs 2G4 and ADI-15946 on the GP base (Howell et al, 2017;West et al, 2019). However, unlike with FVM09, Figure 4.…”
Section: Identification and Functional Properties Of Candidate Cocktamentioning
confidence: 94%
“…base of each protomer of GP CL , and the constant domains were oriented upward from the viral membrane ( Figure 3C). The rE-BOV-520 footprint includes relatively conserved regions including the internal fusion loop (IFL) stem of the GP2 subunit and the hydrophobic pocket formed by five residues of the GP1 subunit and termed previously the ''3 10 '' pocket (Zhao et al, 2016;West et al, 2019). The footprint of rEBOV-520 is distinct from that of the previously described broad human base-specific mAb ADI-15878 West et al, 2018) but is similar to the footprint of the potent human-base-specific mAb ADI-15946 ( Figure 3D), which fully neutralizes EBOV and BDBV but not SUDV (Wec et al, 2017;West et al, 2019).…”
Section: Identification and Functional Properties Of Candidate Cocktamentioning
confidence: 99%
See 1 more Smart Citation
“…Nine solved structures for EBOV glycoproteins are found in the Protein Data Bank (Berman et al 2003) with the following codes: 5JQ3, 6QD7, 6QD8, 6MAM, 6EA7, 5KEL, 5KEN, 6EA5, and 5KEM with a resolution of 2. 23, 3.10, 3.30, 4.10, 4.25, 4.30, 4.30, 4.75, and 5.50 Å, respectively (Ehrhardt et al 2019;Pallesen et al 2016;West et al 2018West et al , 2019. Four of these structures are solved by x-ray crystallography (5JQ3, 6MAM, 6EA7, and 6EA5), while the rest are solved by cryo-electron microscopy.…”
Section: Methodsmentioning
confidence: 99%